Evaluation of anxiolytic potential of Linum usitatissimum oil in wistar rats - Satapathy, Trilochan; Kasture, S. B.; Kurrey, Shekhar Suman; Meher, Bibekananda (Journal of Applied Pharmaceutical Research, 2014)
The objective of the present study was to evaluate the anxiolytic potential of the Linum usitatissimum (Flax seed) oil (5ml and 2.5ml/kg) in wistar rats by using Elevated plus maze (EPM) model and 5ml and 10 ml/kg in Lithium induced head twitches model. Experiments were carried out on white inbred Wistar rats (180-200 g). The efficacy of the oil at both the animal models was compared with the standard anxiolytic drugs Diazepam (0.5 mg/kg). The result showed that the oil significantly increased the number of entries and time spent in the open arm in the elevated plus maze. Similarly in Lithium induced head twitches model administration of oil decreases the no. of head twitches. Present study confirms that the extract showed significant anxiolytic activity at both dose levels which is comparable with standard anxiolytic Diazepam.